Introduction. Anarchism and the national question—historical, theoretical and contemporary perspectives. Issue 1 (28th October 2022) - Gutiérrez, José A; Kinna, Ruth
Abstract: This article provides an introduction to the themed section 'Anarchism and the national question—historical, theoretical and contemporary perspectives.' We discuss first the long and often overlooked engagement of anarchists with the colonial and national liberation question, particularly—but not exclusively—in the heyday of the movement (from the second half of the 19th to the first decades of the 20th century). We discuss in particular the overlaps and tensions between anarchists and republicans (those who favoured republics as opposed to monarchies) and anti‐colonial nationalists (anti‐colonialists who defended the right of national self‐determination). Then we proceed to discuss the potential for a dialogue between anarchist and nationalism studies based on three interventions. First, to problematise the narrative that conflates nations with state‐building processes. Second, to better grasp the emergence of alternatives to the nation–state as a historical construct. Third, to complicate narratives that associate in an unproblematic fashion internationalism and classless society. Finally, the introduction highlights the four questions which lie at the core of the themed section and discuss briefly how the papers relate to these.